Taken - Bowman, Erin (HarperTeen / HarperCollins, 2013)
"In the isolated town of Claysoot, every male is mysteriously "Heisted" on his eighteenth birthday, and seventeen-year-old Gray Weathersby is determined to figure out why"..
Keywords: JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / General; Adventure and adventurers; Brothers; Government, Resistance to; Fantasy; Jugendbuch